TEACHING LISTENING FROM A DISCOURSE PERSPECTIVE (METACOGNITIVE STRATEGY) - Nor, Hidayah (LET: Linguistics, Literature and English Teaching Journal, 2012)
Listening is a process of activities hearing speech symbols by full attention, understanding, appreciation, and interpretation to acquire communication meaning that is delivered by the speaker through speech. Listening constitutes quite important activities in learning language. It is the basis of the learning process as a child learns language from his mother. By using metacognitive strategy, it can help students to compensate their bottom up listening processing and give students an overview of the listening process. This strategy also builds the character of the students to become competence, independent, self-confidence, creative, and responsibility that is related to character building in education in Indonesia. The strategy include extract an important detail from ongoing speech, identify the gist of a segment and then predict what will come next in a segment.